Hybridization and growth of tropical sea urchins - Rahman, Md. Aminur; Arshad, Aziz; Md. Yusoff, Fatimah; Nurul Amin, Sarker Mohammad (Academic Journals, 2013)
Potential for interspecific hybridization between genetically diverged species of tropical sea urchins, Echinometra sp. A (Ea) and Echinometra mathaei (Em) was examined through cross fertilization and hybrid rearing experiments. Mean performance traits of fertilization, larval survival, metamorphosis and recovery of juveniles Em (ova)xEa (sperm) and Ea (ova)xEm (sperm) hybrids were not significantly different from each other but were significantly lower than either of their conspecific control, EaxEa and EmxEm. Despite these, hybrids in both directions were developed normally to sexually mature adults. The growth parameters (final weight, weight gain, gonad weight, gonad index and SGR) of 2-year-old adult hybrids were significantly higher than the superior parent (EaxEa) and inferior parent (EmxEm). The gonad production showed an increment of 45.49% in F1 hybrids over mid-parents, while it showed an increase of 33.74%, 62.60% and 46.76% in F1 hybrid of EmxEa and 31.42, 59.79 and 44.22% in F1 hybrid of EaxEm over the superior, inferior and mid-parents, respectively. Survival was highest in EmxEm followed by EaxEa, EmxEa and EaxEm in that order. Therefore, body growth, gonad production and survival indicate hybrids in either direction were viable in laboratory conditions. The superiority of these growth traits of the hybrid groups over their parental values indicates positive heterosis (hybrid vigor). This study is the first successful demonstration of hybrid vigor between two diverged species of sea urchins. Hence hybrids in both directions appear to have considerable potential for use in aquaculture.